Antibiotic resistances and eradication rates in Helicobacter pylori infection - Gonzalo Botija; Clara García Rodríguez; Aránzazu Recio Linares; Carolina Campelo Gutiérrez; Elia Pérez-Fernández; Alfonso Barrio Merino (Elsevier, 2021)
Introduction: The resistance to antibiotics of Helicobacter pylori (H. pylori) is the main factor that affects current therapeutic treatments. The main objective of this study is to describe the pattern of antibiotic resistances in children with an infection due to H. pylori. Patients and methods: An observational, retrospective study was conducted from 2014 to 2019, which included patients between 5 and 17 years old, on whom a gastroscopy, with a gastric biopsy culture positive for H. pylori, and an antibiotic sensitivity study was performed. The antibiotic sensitivity studies were performed using an epsilometer (E-test). The cut-off points to define the resistances were those proposed by the European Committee on Antimicrobial Susceptibility Testing - EUCAST. The eradication study was performed using the 13C-urea breath test or the H. pylori monoclonal test in faeces 6-8 weeks after finalising the treatment. Results: The study included 80 patients (63.8% females), with a mean age of 11.9 years (SD ± 2.7 DS). Over one-third (38.8%) of the patients had received previous treatment for H. pylori. In the endoscopy, peptic ulcer lesions were observed in 10% of patients. More than two-thirds (67.5%) had resistance to at least one drug. 16.3% presented double resistance. The primary resistances were: clarithromycin, 44.9%, metronidazole 16.3%, levofloxacine 7.9%, and amoxicillin 2%. Patients that received treatment according to the new ESPGHAN 2017 guidelines had significantly higher eradication rates compared to those that received treatment according to previous guidelines (80% vs. 55.8%, P = 0.04). Conclusions: The high rate of H. pylori resistances, and as a result, the low eradication rates, are still a very important cause for concern. The first line treatment, when this is indicated must be given following the antibiotic sensitivity studies, and in the cases where these cannot be done or are not available, at least in accordance with the regional resistance rates. The correct application of the new guidelines significantly improves the eradication rate. Resumen: Introducción: Las resistencias antibióticas de Helicobacter pylori (H. pylori) son el principal factor que afecta a la eficacia de los regímenes terapéuticos actuales. El objetivo principal del estudio es describir el patrón de resistencias antibióticas en ni˜nos con infección por H. pylori. Pacientes y métodos: Estudio observacional retrospectivo de 2014 a 2019 en el que se incluyen pacientes entre 5-17 años a los que se realizó gastroscopia, con cultivo de biopsia gástricapositivo para H. pylori y estudio de sensibilidad a antibióticos. Los estudios de sensibilidad antibiótica se realizaron mediante E-test. Los puntos de corte para definir las resistencias fueron los propuestos por el EUCAST. El estudio de erradicación se realizó con test del aliento con urea marcada con C 13 o test monoclonal de antígeno de H. pylori en heces a las 6-8 semanas de finalizar el tratamiento. Resultados: Ochenta pacientes (63,8% mujeres). Media de edad 11,9 años (±2,7 DS). Un 38,8% habían recibido tratamiento previo para H. pylori. Un 10% presentaron en la endoscopia lesiones ulcerosas pépticas. El 67,5% presentaba resistencia al menos a un fármaco. Un 16,3% presentaron doble resistencia. Las resistencias primarias fueron: claritromicina 44,9%, metronidazol 16,3%, levofloxacino 7,9% y amoxicilina 2%. Los pacientes que recibieron tratamiento acorde a las nuevas guías ESPGHAN 2017 presentaron tasas de erradicación significativamente superiores en comparación con los que recibieron tratamiento acorde a las guías previas (80% vs. 55,8% p = 0,04). Conclusiones: La alta tasa de resistencias de H. pylori y, en consecuencia, las bajas tasas de erradicación, siguen siendo una preocupación muy importante. El tratamiento de primera línea, cuando esté indicado debe hacerse guiado por estudios de sensibilidad antibiótica y en los casos en el que no se puedan realizar o no estén disponibles, al menos de acuerdo con las tasas regionales de resistencia. La aplicación correcta de las nuevas guías mejora de forma significativa el nivel de erradicación.